Profiling X chromosome genes expression relevant to sex dimorphism in stroke: insights from transcriptomics landscape analysis - Qin, Xiu-De; Li, Yue-Rong; Cai, Qian; Liu, Jia-Ye; Dang, Zhao-Hui; Li, Li-Ling; Min, Jia-Wei; Qi, Shao-Hua; Bu, Fan (Frontiers in Genetics, 2025)
IntroductionAlthough age is the most important non-modifiable risk factor for cerebral stroke, it is also apparent that females commonly exhibit longer lifespan and better outcome after stroke compared to the age-matched males. A critical event after stroke is the peripheral infiltration of immune cells across damaged blood-brain barrier, which induces inflammatory and immune responses within the brain parenchyma and consequently worsen brain injury. These events are also dependent on age and display a sex different pattern. Theoretically, X chromosome-encoded differential expression genes (DEGs) may explain differences between the sexes. However, the expression and regulation of these DEGs after stroke have not been studied in detail.MethodsWe conducted three datasets of human blood cells, mice brain, mice microglia and T cells that were previously published, and analyzed the contribution of gender, age and stroke insult on the X chromosome-encoded DEGs.ResultsThe main findings were (i) compared to age, the stroke/hypoxia was a more potent factor in eliciting the DEGs. Particularly, older stroke patients exhibited more changes compared to young stroke group. (ii) After a stroke, the DEGs was diversely influenced by sex, age and cell types being studied. Particularly, either aging or gender led to more striking changes in brain-infiltrating T cells than in the resident immune cells.DiscussionThese findings highlight the complex interplay between sex, age, and immune responses in mediating stroke incidence and outcome. Investigation of the identified X chromosome-encoded genes in brain-infiltrating T cells deserves high priority, as they may play more important roles in explaining gender-related differences in stroke and brain injury.